Persuading the Supreme Court : The Significance of Briefs in Judicial Decision-Making - Hazelton, Morgan L.W; Hinkle, Rachael K. (Book collections on Project MUSE., 2022)
"Each year the public, media, and government wait in anticipation for the Supreme Court to announce big decisions. These opinions have shaped legal policy in areas as important as healthcare, marriage, abortion, and immigration. It is not surprising that parties and outside individuals and interest groups invest an estimated twenty-five to fifty million dollars a year to produce roughly one thousand briefs every year to communicate information to the justices, seeking to impact these rulings. Despite the importance of the Court and the information it receives, many questions remain unanswered regarding the production of such information and its relationship to the Court's decisions. Persuading the Supreme Court leverages the very written arguments submitted to the Court to shed light on both their construction and impact. Drawing on more than 25,000 party and amicus briefs filed between 1984 and 2015 and the text of the related court opinions, as well as interviews with former Supreme Court clerks and attorneys who have prepared and filed briefs before the Supreme Court, Morgan Hazelton and Rachael Hinkle have shed light on one of the more mysterious and consequential features of Supreme Court decisionmaking"--